Assessing the Effectiveness of Mobile-Application Technology: A Project-Based Learning - Sariani, Sariani; Yaningsih, Yaningsih; El Khairat, Mutia (Universitas Muhammadiyah Sidoarjo, 2020)
In the development of technology and its advances in this industrial revolution 4.0 era, the graduates of vocational higher education institution are required to have a ready to use skill as demanded by the job market. This study aimed to investigate the effectiveness of utilizing mobile applications regarding vocabulary acquisition which occurred within a learning process. It was a project-based learning (PBL) performed during the supervision time of the student’ final project applying dictionary applications; The Free Dictionary and Dictionary.com. A mixed method approach was implemented where the data for the quantitative study was collected from the comparison of Vocabulary Size Test (VST) Monolingual-Version A which were carried out prior to and after the PBL. Moreover, the qualitative data was obtained from semi close-ended questionnaire, and open-structured interview. The result shows the superiority of using the mobile apps through this project-based process and at the same time the apps provide contextualized problem-solving environment to their users. HIGHLIGHTS: Even though written reference sources still have a place for students, it cannot be denied that online reference sources have many advantages in the current process of English teaching and learning. Through the project-based learning, mobile application technology can facilitate the students in the language learning process effectively and efficiently, and empower themselves to get maximum results, which is ultimately improve the output of educational institutions in the future.